Forgoing artificial nutrition or hydration at the end of life: a large cross-sectional survey in Belgium. Issue 7 (13th March 2014) - Chambaere, Kenneth; Loodts, Ilse; Deliens, Luc; Cohen, Joachim
Abstract : Objectives: To examine the frequency and characteristics of decisions to forgo artificial nutrition and/or hydration (ANH) at the end of life. Design: Postal questionnaire survey regarding end-of-life decisions (including ANH) to physicians certifying a large representative sample (n=6927) of Belgian death certificates in 2007. Setting: Flanders, Belgium, 2007. Participants: Treating physicians of deceased patients. Results: Response rate was 58.4%. A decision to forgo ANH occurred in 6.6% of all deaths (4.2% withheld, 3.0% withdrawn). Being female, dying in a care home or hospital and suffering from nervous system diseases (including dementia) or malignancies were the most important patient-related factors positively associated with a decision to forgo ANH. Physicians indicated that the decision to forgo ANH had had some life-shortening effects in 77% of cases. There had been no consultation with the patient in 81%, mostly due to incapacity (coma or dementia). The family, colleague physicians and nurses were involved in decision making in 76%, 41% and 62%, respectively. Conclusions: A substantial number of deaths are preceded by a decision to forgo ANH in Belgium. These decisions, ethically laden and involving a considerable chance of life shortening, are mostly not preceded by discussion with the patient despite existing patient rights legislation. It is recommended that physicians and patients and their families alike dedicate ample time to the discussion of treatment options and communication about the possibility of forgoing ANH and that this discussion takes place earlier as part of overall end-of-life care planning rather than at the very end of life.